2007
DOI: 10.1111/j.1474-919x.2007.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual acoustic monitoring of the European Eagle OwlBubo bubo

Abstract: The Eagle Owl Bubo bubo is cited in Annex I of the Birds Directive of the European Union. Europe's biggest owl is extremely sensitive to human presence and needs special conservation measures. The present paper aims to show that monitoring of individuals by bioacoustic methods can be relevant to understanding population dynamics. Our study investigates the possibility of identifying a vocal signature in the wild‐recorded calls of male and female Eagle Owls, and assesses the potential use of these signatures fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 21 publications
1
50
1
Order By: Relevance
“…Hoot calls ("u-hu" calls) of the male Eagle Owl (Bubo bubo) are substantially lower in fundamental frequency than hoot calls of females (Grava et al 2008). The Fig.…”
Section: Order Strigiformesmentioning
confidence: 99%
“…Hoot calls ("u-hu" calls) of the male Eagle Owl (Bubo bubo) are substantially lower in fundamental frequency than hoot calls of females (Grava et al 2008). The Fig.…”
Section: Order Strigiformesmentioning
confidence: 99%
“…4 Distribution of the distances moved by male Corncrakes in the Nurzec River Valley in 2012. When pairs of calls showed a similarity value of greater than 0.98 (Pearson's R), they were considered to come from the same individual estimate of similarity, which is lacking in most studies (e.g., Grava et al 2008;Garcia et al 2012), can be used to discriminate between individuals: two calls with a similarity value of less than 0.90 can be considered to belong to different individuals. Simply put, the features of calls recorded in the same place can reveal whether or not those calls were produced by the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that individual vocal features could be helpful in both monitoring and censusing efforts (Darden et al 2003;Terry et al 2005), especially for secretive and cryptic species (Rebbeck et al 2001;Grava et al 2008). This non-invasive identification method does not require capturing, visually observing, or physically approaching individuals.…”
Section: Introductionmentioning
confidence: 99%
“…As a top predator, rūrū may be vulnerable to toxins used to control introduced mammals (Stephenson et al 1999;Fraser & Hauber 2008). Globally, owls have been shown to be a robust biodiversity indicator of ecosystem health and integrity (Blackburn et al 2001;Anthony et al 2006), and a range of monitoring methods have been developed, including using playback calls (Anthony et al 2006), mouse lures (Imboden 1975), mark-re-sight (Blackburn et al 2001), and acoustic monitoring (Gravia et al 2008).…”
Section: Introductionmentioning
confidence: 99%